IMPLEMENTATION OF CONTEXTUAL TEACHING LEARNING SDN 057214 MUKA PAYA KEC. HINAI - Aina Fauza (Journal of Quality Islamic Education Research, 2025)
This study discusses the effectiveness of the application of Contextual Teaching and Learning (CTL) in the learning of Islamic Religious Education (PAI) subjects at SDN 057214 Muka Paya. This study is a qualitative descriptive study. With a phenomenological approach, this study attempts to understand the reality of events and various activities carried out in the learning process using a contextual approach at the school. The data sources for this study were students at SDN 057214 Muka Paya, PAI teachers. While the research data were obtained through observation, interviews and documentation. The research data were analyzed descriptively qualitatively. Data analysis began with coding, transcription and reduction. The final results of the data analysis revealed that the application of PAI learning with a contextual approach implemented at SDN 057214 Muka Paya was carried out in accordance with the main components of the contextual approach, including: constructivism, discovery, asking, learning communities, modeling, reflection and authentic assessment. In addition to being in accordance with the main components, PAI learning activities using a contextual approach have high effectiveness in supporting students' academic achievement and students' understanding of learning applications in everyday life. The learning carried out becomes meaningful, cheerful and enjoyable (joyfull learning) for students.